A group additivity methodology for predicting the thermochemistry of oxygen‐containing organosilanes. Issue 12 (5th August 2020) - Janbazi, H.; Schulz, C.; Wlokas, I.; Wang, H.; Peukert, S.
Abstract: A combinatorial approach was applied to devise a set of reference Si–C–O–H species that is used to derive group‐additivity values (GAVs) for this class of molecules. The reference species include 62 stable single‐bonded, 19 cyclic, and nine double‐bonded Si–C–O–H species. The thermochemistry of these reference species, that is, the standard enthalpy of formation, entropy, and heat capacities covering the temperature range from 298 to 2000 K was obtained from quantum chemical calculations using several composite methods, including G4, G4MP2, and CBSQB3, and the isodesmic reaction approach. To calculate the GAVs from the ab initio based thermochemistry of the compounds in the training set, a multivariable linear regression analysis is performed. The sensitivity of GAVs to the different composite methods is discussed, and thermodynamics properties calculated via group additivity are compared with available ab initio calculated values from the literature.